2015
DOI: 10.1108/jkm-06-2014-0234
|View full text |Cite
|
Sign up to set email alerts
|

Designing workspaces for cross-functional knowledge-sharing in R & D: the “co-location pilot” of Novartis

Abstract: Purpose – This paper examines co-location as an important solution to design workspaces in research and development (R & D). It argues that co-locating R & D units in multi-space environments serves knowledge creation by leveraging knowledge sharing across boundaries. Design/methodology/approach – This study is based on a co-location project of the knowledge-intensive, multi-national company Novartis. To compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 72 publications
3
54
0
1
Order By: Relevance
“…It crosses distance and organizational structures, resulting in dynamic teams whose members are selected from different workgroups both inside and outside of the company (Pentland 2012;Chen and McDonald 2015). Changes in the communication patterns affect knowledge sharing and innovation processes by leading to the emergence of cross-pollination of ideas between workgroups and to the need for continuous coordination across functions (Hill and Gareth 2009;Fleming 2004;Coradi et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…It crosses distance and organizational structures, resulting in dynamic teams whose members are selected from different workgroups both inside and outside of the company (Pentland 2012;Chen and McDonald 2015). Changes in the communication patterns affect knowledge sharing and innovation processes by leading to the emergence of cross-pollination of ideas between workgroups and to the need for continuous coordination across functions (Hill and Gareth 2009;Fleming 2004;Coradi et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…As Yeo and Marquardt (2015) state, it is a cognitive and behavioural process involving individuals. To be able to stimulate tacit KS, organisations need to understand how knowledge is shared between employees (Coradi et al, 2015) and thus how to measure behaviour that ensures that knowledge is shared. With regard to the cognitive element of the process, involvement is mentioned as an important aspect (e.g., Hau et al, 2016;Mascitelli, 2000).…”
Section: Knowledgementioning
confidence: 99%
“…Knowledge flows within organisations are important for successful innovation (Coradi, Heinzen, & Boutellier, 2015) and competitive advantage (Carlucci & Schiuma, 2006). Increased knowledge sharing (KS) is highly associated with success of new product development (NPD) programmes (Markham & Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Granovetter (1973) maintains that weak tie sources are often more important in spreading information or resources because they tend to serve as a bridge between otherwise disconnected social groups. Following that line of thought, Coradi, Heinzen, and Boutellier (2015) points out that as weak tie sources have a low degree of connectivity, they do not provide the deep social support of dense networks; thus such sources provide more opportunities to secure new information and diverse perspectives that can facilitate ideas (Fleming, Mingo, & Chen, 2007). Previous research has also found that weak tie sources transfer and secure codified knowledge efficiently and easily (Hansen, 1999).…”
Section: Antecedents Of Breadth Of Absorptive Capacitymentioning
confidence: 99%
“…Our results are consistent with previous studies. Prior related knowledge is the most important antecedent to absorptive capacity (Cohen & Levinthal, 1990;Van Den Bosch, Volberda, & De Boer, 1999) and weak tie sources contain the breadth of knowledge resources (Coradi, Heinzen, & Boutellier, 2015); therefore, a larger knowledge breadth and network of weak ties will have more nodes and provide broader sources of knowledge to breadth of absorptive capacity. Many studies have shown that prior related knowledge is important to absorptive capacity (Cohen & Levinthal, 1990;Van Den Bosch, Volberda, & De Boer, 1999) and that strong tie sources are greatly beneficial in the acquisition of useful (tacit and specialized) knowledge (Szulanski, 1996;Uzzi, 1997;Hansen, 1999).…”
Section: Theory Contributionmentioning
confidence: 99%